Investigate and Compare the Frequency of Anemia in Breast Fed Children and Cow Milk Fed Children - Muhammad, Fawad; Hussain, Mohammad; Ahmad, Ijaz; Khan, Aslam (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
OBJECTIVES: To determine the frequency of anemia in breastfed children and cow milk-fed children METHODOLOGY: This is a Cross-sectional study. A total of 239 Infants aged 1 month to 12 months of both genders on breastfeeding or cow milk feeding were enrolled using a non-probability consecutive sampling technique at Pediatric Medicine, Lady Reading Hospital MTI, Peshawar. This study was conducted from 30th November 2020 to 29th May 2021 after approval of the hospital’s ethical committee and written informed consent of parents. 5 ml of venous blood was drawn under an aseptic measure and was sent to the hospital laboratory for hemoglobin levels. Hemoglobin level was noted in all children including breast and cow-milk fed. The frequency of anemia was noted in all patients. Data was entered and analyzed using SPSS 22. RESULTS: In our study total of 239 infants were enrolled with a mean age of 7.57±3.4 months. There were 45.8% male infants and 54.4% female infants. The mean weight was 6.9±2.1 kg and the mean length was 60.4±5.4 cm. The mean hemoglobin level was 6.9±2.9g/dl. Malnutrition was present in 46% of infants. Anemia was present in 58.6% of infants. Anemia was more common in patients having cow milk feed as compared to mother feed, 83.3% versus 33.6%, p-value <0.001. CONCLUSION: The results of the study suggest that anemia is significantly higher in cow milk-fed infants compared to breastfed infants. Hence exclusive breastfeeding should be prioritized to reduce anemia risk in infancy.